ROLE OF RELIGIOUS SCHOOLS, IN THE LIGHT OF DR۔ MAHMOOD AHMAD GHAZI’S OPINIONS - Mahboob-urr-Rahman Qureshi; Fakhar Ud Din (دی اسکالر, 2016)
Dr. Mahmood Ahmad Ghazi’s personality does not need any introduction; rather his publication and services to Islam are enough to introduce him. In addition to his numerous publications, like the world famous Muhadhraat, Dr. Ghazi served on a number of prominent positions including the Justice of Shariat Court, Member of Islamic Ideology Council, Faculty member and fellow at various international universities (including Qatar University), Member Advisory board of State Bank, and Federal Minister for Religious Affairs. In his diverse scholarly career, Dr. Ghazi  providing illuminating guidance on a number of organizational, socio-cultural and theological issues faced by the Islamic ummah. One of the institutions where these three aspects synergize with each in order to serve one of the most eminent needs of our Ummah is the institution of Islamic seminaries or the deeni madaris. These seminaries have a pivotal role in the transformation and maintenance of culture and norms of our society. The Islamic knowledge and practices that we see  flouring in our society is a glaring contribution of these institutions. Dr. Mehmood Ahmad Ghazi had a lifelong association with these institutions and he left no stone unturned for their betterment. As a renowned scholar, educationist, and federal minister, he duly highlighted the importance of these seminaries in national and international forums. However, he was also a strong advocate of reforms in these institutes. He stressed the administrators of these seminaries to modify the curriculum by including modern and scientific subjects, to keep pace with the rapidly changing world. He was of the view that graduates of these institutes must be able to compete with university graduates in every sphere of life. In short, Dr. Ghazi’s ideas are thought-provoking, inspiring, and attuned to the needs of the modern era. He gave new dimensions to various fields of Islamic scholarship and his personality serves as a beacon for the Muslim youth and their leadership.